Тhe use of radionuclide methods for contemporary diagnostic in angiology - Lacko, Anton; Rutowski, Jan Antoni (Актуальні проблеми транспортної медицини, 2017)
Apart from radiology, ultrasonography and pletysmography methods there are used also radionuclide methods in angiology diagnostics. In initial phases of vascular diseases there are present changes in functional character together with changed microcirculation. The aim of presented work is to point out on nuclear medicine methods, which enable to diagnose early phases of angiopathy, especially in lower extremities, by non-invasive way. Крім методів радіології, ультрасонографії та плетизмографії в ангіології в діагностиці використовують також радіонуклідні методи На початкових етапах судинних захворювань спостерігаються зміни функціонального характеру разом зі зміненою мікроциркуляцією. Мета представленої роботи — вказати методи ядерної медицини, які дозволяють діагностувати ранні фази ангіопатії, особливо в нижніх кінцівках, неінвазивним способом. Помимо методов радиологии, ультрасонографии и плетизмографии в ангиологи в диагностике используют также радионуклидные методы На начальных этапах сосудистых заболеваний наблюдаются изменения функционального характера вместе с измененной микроциркуляцией. Цель представленной работы — указать методы ядерной медицины, которые позволяют диагностировать ранние фазы ангиопатии, особенно в нижних конечностях, неинвазивным способом.